NATIONAL STORIES SCENARIO / PORTUGAL - Lucas, Maria Raquel (2015)
Continuum Naturale was founded in order to coordinate and develop technical, scientific and entrepreneurial efforts oriented toward an improvement of nature integration in urban and rural environments; to encourage, coordinate and facilitate the investigation, teaching, advice and diffusion of all aspects related to the improvement of nature integration in urban and rural areas; and to promote the development and improvement of techniques and practices used in the improvement of nature integration in urban and rural areas.